A novel mitovirus detected in Diaporthe rudis, a fungus associated with Phomopsis dieback on grapevines - Kocanová, Mária; Eichmeier, Aleš; Botella, Leticia (Archives of virology, 2020)
The genome sequence of a mitovirus found in an isolate of Diaporthe rudis, one of the causal agents of Phomopsis dieback on grapevines, was determined by two high-throughput sequencing approaches, small RNA and total RNA sequencing. The genome of this mitovirus is 2,455 nt in length and includes a single large open reading frame (ORF) encoding an RNA-dependent RNA polymerase (RdRp). A BLASTx comparison of the full-length genome sequence showed the highest similarity (54.15%) with that of Colletotrichum falcatum mitovirus 1 (CfMV1). Our results reveal a new member of the genus Mitovirus first detected in D. rudis (Fr.) Nitschke, with the proposed name "Diaporthe rudis mitovirus 1" (DrMV1).
Keywords: Genome Size; Open Reading Frames; exprese genu; Phylogeny; Gene Expression; Saccharomycetales; Plant Diseases; Fungal Viruses; Viral Proteins; genom virový; Whole Genome Sequencing; mykoviry; sekvenování celého genomu; virové proteiny; Genome, Viral; délka genomu; RNA-Dependent RNA Polymerase; fylogeneze; nemoci rostlin; Vitis; RNA-dependentní RNA-polymerasa; otevřené čtecí rámce